Model Pengembangan Penguatan Pendidikan Karakter dan Literasi Lingkungan - Supriyanto, Agung (Universitas Negeri Malang, 2020)
This study aimed to describe the planning, the implementation, and the obstacles and impacts of the development model for strengthening character education and environmental literacy in SMP Negeri 3 Malang. This study used a qualitative approach to the type of descriptive study. The plans were formulating priorities for the main values of strengthening character education and environmental literacy, formulating development programs, and socializing to all schools, parents, and the community. The programs were habituation activities under five main values, namely religious, nationalist, independent, integrity, and cooperation. There were obstacles in implementing the program that had been overcome properly. The implementation of the program to strengthen character education and environmental literacy had a good impact on schools, students, and parents.